KOMUNIKASI INTERPERSONAL ANTAR ETNIS (Studi Kasus Komunikasi Antar Personal Etnis Nias, Mentawai, dan Minang di Kampus Universitas Ekasakti) - Ardi, Syaiful (Universitas Ekasakti, 2022)
Ethnic is a social group that has the same cultural and historical traditions, and because of that similarity they have an identity as a subgroup in a wider society. Usually the members of these groups are different from the culture of the people around them because they have certain cultural characteristics from other members of the community such as having their own language, customs, and even their own religion. In this ethnicity or culture, there are many differences such as in terms of religion, language, race and ethnicity. Even intercultural communication is a process of sharing information, ideas or feelings among those with different cultural backgrounds. This study used qualitative research methods. The research subjects were selected using a purposive sampling technique, namely 5 from the Nias ethnic group, 5 from the Mentawai ethnic group and 5 from the Minang ethnic group. To get the data, the writer uses 4 data collection techniques, namely participatory observation (passive, moderate, active and complete participation), interviews, and document studies. The results of this study indicate that interpersonal communication theory becomes a process of interaction between two people which is carried out face to face or through the media. Therefore, in other words, a dialogue or conversation that occurs between two people is personal, direct and intimate. Interpersonal communication (interpersonal) in a different culture between the Nias, Mentawai and Minang ethnic groups is not entirely applied in life, even from these ethnic differences there are still misunderstandings that occur. The way so that there are no more misunderstandings between ethnic groups, then between ethnic groups can maintain inter-ethnic harmony, namely not mocking each other, not blaming each other and should understand each other. Constraints in interpersonal communication between ethnic groups in the form of communicating or associating. To prevent this from happening, the efforts made are to recognize each other, interact a lot between ethnicities, and even do positive activities together. So that misunderstandings in communication do not occur.